Observations for Assertion-based Scenarios in the context of Model Validation - Aydal, Emine; Paige, Richard; Woodstock, Jim (Electronic Communications of the EASST, 2008)
Certain approaches to Model-Based Testing focus on test case generationfrom assertions and invariants, e.g., written in the Object Constraint Language. Insuch a setting, assertions and invariants must be validated. Validation can be carriedout via executing scenarios wherein system operations are applied to detect unsatisfiedinvariants or failed assertions. This paper aims to improve our understanding ofhow to write useful validation scenarios for assertions in OCL. To do so, we reporton our experiences during the creation and execution of 237 scenarios for validatingassertions for the Mondex Smart Card application. We also describe key factors thatmust be considered in transforming scenarios into test cases.